Understanding the Formation Process of Perovskite Layers Grown by Chemical Vapour Deposition - Moser, T.; Kothandaraman, R.; Yang, S.; Walter, A.; Siegrist, S.; Lai, H.; Gilshtein, E.; Tiwari, A. N.; Fu, F. (Frontiers in Energy Research, 2022)
This work aims at extending the understanding of the formation processes of (Cs0.07FA0.93)PbI3 perovskite layers deposited by a two-step vapour method. In a first step, an inorganic CsI/PbI2 precursor stack is deposited by thermal evaporation (TE). A chemical vapour deposition (CVD) is then used to convert the precursor into the perovskite layer by reaction with a chemical vapour of formamidinium iodide (FAI). Here we show how crystallinity and morphology of the TE precursor layer are both influenced not only by the substrate surface properties but also by the thermal treatment in the initial phase of the CVD process. Furthermore, we provide insights on the evolution of perovskite film formation and show how a uniform elemental composition is achieved by the diffusion of cesium through PbI2 during the CVD conversion reaction.